2010
DOI: 10.1111/j.1750-3841.2010.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Edible Mushroom (Flammulina velutipes) Extract Inhibits Melanosis in Kuruma Shrimp (Marsupenaeus japonicus)

Abstract: This study compared the potential of an aqueous extract of an edible mushroom (Flammulina velutipes) to prevent melanosis in cultured Kuruma shrimp (Marsupenaeus japonicus) with other antimelanosic compounds in vivo. The mushroom extract contained 9.1 mg/mL ergothioneine (ESH). Immersion of live full-grown shrimp in a 0.5% w/v solution of mushroom extract significantly reduced PPO activity in shrimp hemolymph. In addition, expression of the prophenoloxidase (proPO) gene decreased in hemocytes, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 20 publications
2
25
0
1
Order By: Relevance
“…Similar results were obtained from the extracts from Punica granatum and Leucaena leucocephala which showed the effect of inhibition of melanosis formation in Pacific white shrimp during iced storage (Nirmal and Benjakul, 2011a;Fang et al, 2013) and the extract from the edible mushroom Flammulina velutipes which significantly inhibited the formation of melanosis of shrimp and crab (Encarnacion et al, 2010(Encarnacion et al, , 2011a(Encarnacion et al, , 2011b(Encarnacion et al, , 2012.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Similar results were obtained from the extracts from Punica granatum and Leucaena leucocephala which showed the effect of inhibition of melanosis formation in Pacific white shrimp during iced storage (Nirmal and Benjakul, 2011a;Fang et al, 2013) and the extract from the edible mushroom Flammulina velutipes which significantly inhibited the formation of melanosis of shrimp and crab (Encarnacion et al, 2010(Encarnacion et al, , 2011a(Encarnacion et al, , 2011b(Encarnacion et al, , 2012.…”
Section: Resultssupporting
confidence: 68%
“…Phenol polymerization is mainly initiated by the action of an enzymatic complex-PPO (Alasalvar et al, 2011 (Nirmal and Benjakul, 2012b). Natural compounds such as ergothioneine from mushroom, mimosine from lead (Leucaena leucocephala) was shown to inhibit the PPO of shrimp and crab Benjakul, 2011a, 2011c;Encarnacion et al, 2011aEncarnacion et al, , 2011bEncarnacion et al, , 2012. Phenolic compounds such as catechin and ferulic acid and plant extract rich in polyphenol such as pomegranate peel extract also appears to inhibit the PPO of shrimp and be a good alternative for sulphiting agent for retarding melanosis in crustaceans (Fang et al, 2013;Nirmal and Benjakul, 2012b).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that natural extracts or natural compounds including catechin, ferulic acid, extracts from Punica granatum, Leucaena leucocephal and Flammulina velutipes could inhibit the melanogenesis of shrimp during storage in ice (Encarnación et al, 2010(Encarnación et al, , 2011Fang et al, 2013;Nirmal & Benjakul, 2009b, 2011b. The melanogenesis was significantly inhibited and visual quality was significantly improved in Pacific white shrimp treated with GTE in the present study.…”
Section: Resultssupporting
confidence: 59%
“…Previous studies have shown that natural extracts or natural compounds could inhibit the melanogenesis of shrimp during iced storage (Encarnacion et al, 2010;Encarnacion et al, 2011;Fang et al, 2013;Nirmal & Benjakul, 2009b, 2011b. Our previous study showed that melanosis was significantly inhibited in the Pacific white shrimp treated with various concentration of PPE (Fang et al, 2013).…”
Section: Resultsmentioning
confidence: 89%